Sistema de suporte multicamada na realidade brasileira: formação para modular os apoios às necessidades dos estudantes - Costa, Juliane Dayrle Vasconcelos da (Universidade Federal de São Carlos, 2024)
During the two years of the Covid-19 pandemic, society faced a scenario marked by uncertainties, losses, and fears, affecting different sectors of society, including education. With the return of in-person activities, new challenges and tensions arose, both for teachers and students, regarding ensuring participation and promoting learning for all. Given the magnitude of these challenges in the current context, and recognizing the need for schools to reorganize in order to offer adequate support, services, and assistance to meet the demands of diversity, the use of innovative proposals for this new context became timely.In light of this, the present research has the general objective of developing, implementing, and evaluating a training program on the Multi-tiered System of supports (MTSS) for education professionals, aiming to contribute to their professional performance and training, thus promoting greater accessibility for students with and without disabilities. The specific objectives are: a) To develop a training program on MTSS for professionals working in education; b) To describe and analyze an innovation plan on MTSS, built collaboratively between trainers and participants; c) To evaluate the impacts of the training program on the class, the school, and the municipal network based on the professionals' perceptions; d) To assess the limitations and contributions of the MSS proposal in expanding the school's capacity to respond to the diversity of students.This study adopts a qualitative, exploratory approach, using a collaborative action research design. Thirty-eight professionals from the municipal network of a city in the state of São Paulo participated in the research. The study was conducted in three stages: 1) Planning a training program on the Multi-tiered System of supports; 2) Implementing the training program on the Multi-tiered System of supports; and 3) Evaluating the training program on the Multi-tiered System of supports. Data collection was predominantly carried out in virtual environments, through formative meetings and focus groups. An Innovation Plan to Promote the Multilayered Support System was collaboratively developed to be implemented in a challenging class, referred to in this study as "Girassol."After data collection, the material was edited, transcribed, and later analyzed through Content Analysis (CA), and categorized into three main categories: Innovation plan based on MSS; Impact of the training program; and Evaluation of the training program on MTSS. Overall, the results showed an appropriation of the concepts and principles of MTSS, which was fundamental for the development and implementation of the Innovation Plan to Promote MTSS. Significant changes were observed in the Girassol class, in the school, and in the municipal education network. Additionally, the program was well received by the participants, with positive evaluations.
Multi-tiered support system in the brazilian context: training to tailor support to student´s needs
Keywords: Educação especial; Programa de formação; Ensino para todos; Sistema de suporte multicamada; Special education; Training program; Teaching for all; Multi-tiered system of supports; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO